The low‐prevalence Rh antigen STEM (RH49) is encoded by two different RHCE*ce818T alleles that are often in cis to RHD*DOL. Issue 3 (28th June 2012) - Reid, Marion E.; Halter Hipsky, Christine; Hue‐Roye, Kim; Coghlan, Gail; Olsen, Coral; Lomas‐Francis, Christine
<x xml:space="preserve">Abstract</x> BACKGROUND: STEM (RH49) is a low‐prevalence antigen in the Rh blood group system. A scarcity of anti‐STEM has precluded extensive study of this antigen. We report that two alleles with a RHCE*ce818C>T change encode a partial e, and a hrS−, hrB+, STEM+ phenotype and that both alleles are frequently in cis to RHD*DOL1 or RHD*DOL2. STUDY DESIGN AND METHODS: Blood samples were from donors and patients in our collections. Hemagglutination, DNA, and RNA testing was performed by standard techniques. RESULTS: Fourteen STEM+ samples were heterozygous RHCE*ce818C/T: six had RHCE*ceBI and eight had a novel allele, RHCE*ceSM. Eleven were heterozygous for RHD*DOL1 or RHD*DOL2. Eleven samples, previously typed STEM−, had RHCE*ce818C/C (consensus nucleotide). RBCs from informative STEM+ samples were e+/− hrS− hrB+. One person who was heterozygous RHCE*ceBI and RHCE*cE had an anti‐e‐like antibody in her plasma, and one person, who was hemizygous for RHD*DOL2, had anti‐D in her plasma. CONCLUSIONS: We show that two alleles with a RHCE*ce818C>T change (RHCE*ceBI and RHCE*ceSM) encode a hrS− hrB+ STEM+ phenotype. In addition, both alleles are frequently in cis to RHD*DOL1 or RHD*DOL2 and RHCE*ceBI encodes a partial e antigen. In the small cohort of samples tested, RHD*DOL invariably traveled with RHCE*ce818T. Our study also confirmed the presumption that RHD*DOL2, like RHD*DOL1, encodes a partial D antigen and the low‐prevalence antigen DAK.